Analysis of Ancient Empires and Religious Movements: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
As religion lost its former vitality, the society also lost its earlier strength. Caste system destroyed the concept of human equality and divided men into sections. Sub-castes began to multiply in number.For vast majority of men, prevailing social systems were oppressive and painful. The lower classes such as the Sudras lived a life of degradation. The Kshatriyas and the Vaishyas, too, suffered from the domination of the Brahmins, and came to dislike the predominance of the latter.